Disaster Risk Reduction and Climate Change Adaptation: - Ishiwatari, Mikio; Sasaki, Daisuke (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
A multidisciplinary approach that involves multiple sectors and stakeholders is essential for disaster risk reduction and adaptation to climate change. This Special Issue explores how interdisciplinary approaches could resolve a wide range of issues, including risk and damage assessment, behavior change, investment, and evidence-based policy formulation.